1, 1′‐Nitramino‐5, 5′‐bitetrazoles. Issue 14 (24th February 2016) - Fischer, Dennis; Klapötke, Thomas M.; Stierstorfer, Jörg; Szimhardt, Norbert
Abstract: 1, 1′‐Dinitramino‐5, 5′‐bitetrazole and 1, 1′‐dinitramino‐5, 5′‐azobitetrazole were synthesized for the first time. The neutral compounds are extremely sensitive and powerful explosives. Selected nitrogen‐rich salts were prepared to adjust sensitivity and performance values. The compounds were characterized by low‐temperature X‐ray diffraction, IR and Raman spectroscopy, multinuclear NMR spectroscopy, elemental analysis, and DTA/DSC. Calculated energetic performances using the EXPLO5 code based on calculated (CBS‐4M) heats of formation and X‐ray densities support the high performances of the 1, 1′‐dinitramino‐5, 5′‐bitetrazoles as energetic materials. The sensitivities toward impact, friction, and electrostatic discharge were also explored. Most of the compounds show sensitivities in the range of primary explosives and should only be handled with great care! Abstract : Dig for fire : 1‐Nitraminobitetrazoles are a class of very high performance explosive materials with potential application as heavy‐metal‐free primary explosives. Now the corresponding 1‐nitramino‐azobitetrazoles, which are even more powerful but also more sensitive, have been synthesized.